GLOBAL COMPETITIVE POSITIONING OF UZBEKISTAN'S TOURISM SECTOR: A DISTANCE-TO-FRONTIER DIAGNOSIS ACROSS THIRTEEN DEVELOPMENT PILLARS - B. Sobirov (Proceeding of International Conference on Social Science and Humanity, 2026)
Objective: Aggregate competitiveness rankings indicate a destination's overall standing but not where, and by how much, it falls short of attainable global performance. Method: This study applies a distance-to-frontier methodology to position Uzbekistan's tourism sector against the world best-in-class on each of thirteen Travel and Tourism Development Index pillars, using Uzbekistan's 2024 global ranks and pillar indices benchmarked to the highest-scoring economy on every pillar. Results: Uzbekistan attains an overall index of 3.76 (global rank 78), but the pillar-level diagnosis reveals that its largest absolute shortfalls fall not on its lowest-ranked relative weaknesses alone but on its resource pillars: the gap to the frontier is widest for cultural resources (3.19 points, versus Italy), natural resources (3.03, versus Mexico) and tourist-services infrastructure (2.80, versus Cyprus). Conversely, the smallest distances arise on human resources, environmental sustainability and price, where the global frontier is itself comparatively compressed. Novelty: The analysis reframes the competitiveness agenda from closing relative peer gaps to valorizing under-exploited resource endowments and upgrading service infrastructure toward attainable international benchmarks, and it supplies a transparent, pillar-specific target-setting instrument.